Peningkatan Kemampuan Numerasi Siswa Menggunakan Model Realistic Mathematics Education Berbantuan Media PaPinBilCa - Hasanah, Noor Laily; Riswari, Lovika Ardana; Fakhriyah, Fina (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
This study aims to describe how students' numeracy skills improve through the application of the Realistic Mathematics Education (RME) model with the assistance of PaPinBilCa media in grade V at SDN 03 Jojo. SDN 03 Jojo has a low level of numeracy skills, as indicated by the pre-cycle results showing the lowest math score of 40 and the highest of 80, with an average score of 68. This research is a classroom action research involving all 10 students as the sample. The variables studied are the Realistic Mathematics Education (RME) model as the independent variable and numeracy skills as the dependent variable. Data were collected through pre-research interviews, observations, tests, and documentation. Data analysis was conducted quantitatively. In the pre-cycle, 40% of students reached the passing score with an average score of 58.60. After cycle I, the percentage of students who passed increased to 50% with an average score of 74.90. In cycle II, all students achieved a passing score of 100% with an average score of 92.50. The results of the study indicate that the use of the Realistic Mathematics Education model with PaPinBilCa media successfully improved students' numeracy skills, with the initial pre-cycle percentage of 40% increasing to 50% in cycle I and further rising to 100% in cycle II